A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group - Santos, José N. A. Dos Junior; Silveira, Orlando T.; Carpenter, James M. (Zootaxa, 2017)
A new species of Neotropical social wasp, Protopolybia lidiae Santos & Silveira, sp. nov. (Brazil: Pará) is described and illustrated. The hitherto unknown male of P. minutissima (Spinola, 1851) and the nest of P. clypeata Santos, Silveira & Carpenter, 2015, are described. Additional information on nest variation and new collection records are presented for other species of the exigua species-group.